The Use of Singing Method to Strengthen Sundanese Language Competence in Basic Education Students - Ai Sri Masfuroh; Ibnu Imam Al Ayyubi; Asa Ismia Bunga Aisyahrani (GENIUS: Journal of Elementary Pedagogy and Innovation Studies, 2025)
The Sundanese language skills of elementary school students need to be strengthened through engaging and effective learning approaches. One alternative utilized in this study is the singing method using Sundanese-language songs. This research aims to examine whether the application of the singing method can enhance the Sundanese language skills of elementary school students at Darul Amanah Elementary School, West Bandung Regency. The population consisted of students enrolled in the school, with a sample of 20 students in the experimental class and 17 students in the control class selected through purposive sampling. This study employs a quantitative approach with an experimental method and a quasi-experimental design using a non-equivalent control group structure. Data analysis includes descriptive and inferential statistical techniques assisted by SPSS version 26. The findings indicate that, although both groups showed improvement, there was no significant difference between the experimental and control classes in terms of Sundanese language skill mastery. The independent samples t-test result shows a significance value greater than 0.05, indicating no statistically significant difference. Thus, the singing method did not demonstrate a higher effectiveness compared to conventional learning methods in improving Sundanese language skills among elementary school students. Further studies are recommended to explore different learning strategies or additional influencing factors to obtain more optimal outcomes.